A Descriptive Survey of Why Parents Choose Hybrid Homeschools. Issue 3 (2nd July 2016) - Wearne, Eric
ABSTRACT: "Hybrid home schools" are schools in which students attend school with other students for 2 or 3 days per week in traditional classroom settings, and are homeschooled the balance of the week. This exploratory study presents self-reported reasons parents choose these schools, using an electronic survey of parents from four such schools ( n  = 136; 19% return rate). Findings indicate that families in these schools are relatively wealthier and more suburban than parents using tax credit programs, that they value school structures more than particular student achievement outcomes, and that they seek information on accreditation, curriculum, and the religious nature of schools in making their choices.